(untitled) (Revista Brasileira Multidisciplinar, 2026)
The objective of the present study was to evaluate the materials used to treat intraosseous perforations during endodontic treatment., through an integrative literature review. Searches for studies on the topic were carried out through the PubMed/MEDLINE, Virtual Health Library (VHL) and CAPES journal portal databases, covering the period of the last 10 years, with no restrictions regarding language. The descriptors used included a combination of terms: “Root canal preparation” and its derivatives, in addition to terms related to root canal drilling and its treatment. To join the search terms, the Boolean operators “AND” and “OR” were used. Considering the inclusion criteria, the search resulted in 991 studies. After reading the title and abstract, 15 potentially eligible studies were included for full analysis. And, after complete reading, seven studies were included in the literature review. Analysis of the studies showed that the materials used to treat dental perforations are calcium silicate-based cements, such as MTA and Biodentine, due to their physical, chemical, mechanical and biological properties. And, what properties such as sealing capacity, porosity, biocompatibility and bioactivity influence the success of the treatment. Finally, the studies highlight that, in addition to knowledge about the properties of different materials, it is essential that the dentist knows how to identify the location, size and time of occurrence of the perforation, allowing the problem to be resolved and the treatment to be successful.